2020
DOI: 10.1101/2020.07.12.199869
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of syndapin-2 mediated transcytosis across the blood-brain barrier on amyloid-β accumulation in the brain

Abstract: A faulty transport of amyloid-β (Aβ) across the blood-brain barrier (BBB), and its diminished clearance from the brain, contributes to neurodegenerative and vascular pathologies, including Alzheimer’s disease (AD) and cerebral amyloid angiopathy, respectively. At the BBB, Aβ efflux transport is associated with the low-density lipoprotein receptor-related protein 1 (LRP1). However, the precise mechanisms governing the Aβ transport across the BBB, in health and disease, remain to be fully understood. New evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 77 publications
(191 reference statements)
1
2
0
Order By: Relevance
“…Interestingly, our recent study demonstrated that PACSIN-2 participates in the formation of tubular carriers for a fast transcytosis of LRP1 across BECs [7]. Furthermore, we also demonstrated that BECs employ PACSIN-2 for the clearance of amyloid-ß via LRP1 across the BBB [84]. Hence, our findings corroborate the hypothesis that PACSIN-2 facilitates a tubulation-mediated mechanism for transcytosis across BECs.…”
Section: Endocytosissupporting
confidence: 88%
See 1 more Smart Citation
“…Interestingly, our recent study demonstrated that PACSIN-2 participates in the formation of tubular carriers for a fast transcytosis of LRP1 across BECs [7]. Furthermore, we also demonstrated that BECs employ PACSIN-2 for the clearance of amyloid-ß via LRP1 across the BBB [84]. Hence, our findings corroborate the hypothesis that PACSIN-2 facilitates a tubulation-mediated mechanism for transcytosis across BECs.…”
Section: Endocytosissupporting
confidence: 88%
“…Surprisingly, even though BAR proteins and the GC are intrinsically associated with cell membranes and known to control the shape of the membrane, their role is often neglected in the brain endothelium. Numerous BAR proteins are enriched in a mammalian brain, and particular BAR proteins have been reported to be altered in CNS disorders, such as Alzheimer’s [ 29 , 84 ] and Huntington’s [ 127 , 128 ] disease, and epileptic seizures [ 129 ]. Thus, it appears that BAR proteins may have an important role in the brain that is worth further exploring.…”
Section: Conclusion and Future Remarksmentioning
confidence: 99%
“…Aβ40 peptide (Bachem 4014442.1) was prepared into oligomer and fibril samples using previously described methods (44, 45, 57). The samples were characterized first using conventional solid-state TEM to confirm that the oligomers and fibril structures had formed as expected.…”
Section: Methodsmentioning
confidence: 99%